2023
DOI: 10.3389/fcimb.2023.1166389
|View full text |Cite
|
Sign up to set email alerts
|

Microbial characterization of the nasal cavity in patients with allergic rhinitis and non-allergic rhinitis

Abstract: IntroductionAlthough recent studies have shown that the human microbiome is involved in the pathogenesis of allergic diseases, the impact of microbiota on allergic rhinitis (AR) and non-allergic rhinitis (nAR) has not been elucidated. The aim of this study was to investigate the differences in the composition of the nasal flora in patients with AR and nAR and their role in the pathogenesis.MethodFrom February to September 2022, 35 AR patients and 35 nAR patients admitted to Harbin Medical University’s Second A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The nasal microbiota plays a crucial role in the host immune responses, involved in the episode of diseases. Recently, it has been reported that increased Proteobacteria accompanied by decreased Bacteroidetes at the phylum level in nasal microbiota were involved in the pathogenesis of allergic diseases in China ( 17 ). Consistent changes were also observed in the nasal microbiota of prolonged mask wearers in our study, suggesting that long-term use of masks may bring potential risk of such disease.…”
Section: Discussionmentioning
confidence: 99%
“…The nasal microbiota plays a crucial role in the host immune responses, involved in the episode of diseases. Recently, it has been reported that increased Proteobacteria accompanied by decreased Bacteroidetes at the phylum level in nasal microbiota were involved in the pathogenesis of allergic diseases in China ( 17 ). Consistent changes were also observed in the nasal microbiota of prolonged mask wearers in our study, suggesting that long-term use of masks may bring potential risk of such disease.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Che et al attempted to characterize and compare the nasal microbiome of individuals with allergic rhinitis to those who were unaffected. Findings from their study revealed that the presence of species such as Vibrio vulnificus and Acinetobacter baumanni in the nasal microbiome allergic individuals led to an increase in allergic mediators (e.g., GM-CSF, IFN β , IL-27, IL-1β), leading to allergic rhinitis and asthma ( 97 ). Differences in the microbial composition of individuals with respiratory allergies were evident in the nasopharyngeal microbiome, presenting a possible predictor for allergic disease progression in early childhood.…”
Section: Microecological Factors Associated With Allergic Diseasementioning
confidence: 99%